The effect of the circular house model on understanding the scientific concepts of the students of the basic stage at Hreima School for Girls in Irbid Governorate - Jordan - Hattab, Khawla Zuhdi (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to uncover the effect of using the circular house model in understanding the scientific concepts of the basic stage students in the light of their scientific orientation. The study used the semi-experimental method. The study sample was 51 students who were selected from the Huraima Secondary School for Girls in Irbid Governorate and randomly distributed to two groups; a pilot was studied in the circular house and a female officer was studied in the usual manner. The tools of the study were to test the understanding of scientific concepts, and the scale of scientific leanings. To answer the study questions, use the ANCOVA (2x2). The results showed that there were statistically significant differences at the level of (α = 0.05) for the performance of the students in the test of understanding the scientific concepts due to the method of teaching the circular house. The average performance of the control group was 20.82 versus 27.22 for experimental, with an average difference of 6.4 for the experimental group. There were no statistically significant differences in the performance of the students on the understanding of scientific concepts due to scientific trends, A statistical indication of the performance of the students on the test of understanding of concepts is due to the interaction between teaching method and scientific tendencies. In light of the results, the study recommended adopting the circular house model in teaching science, including it in pre-service and in-service teacher training programs, and conducting more studies on the circular house in educational and other variables.
Keywords: the circular house model; understanding scientific concepts; the basic stage; scientific tendencies